Does Anyone Care? Cohesion Policy Issues in Sub-national Politics - Martin Gross (JCMS: Journal of Common Market Studies, 2021)
A key element of the European Union's (EU) attempt to foster citizens' EU identification is its goal to improve citizens' quality of life via its Cohesion policy (CP). Although recent findings demonstrate that the allocation of CP money positively affects sub-national parties' positions on EU integration and CP, we still do not know if sub-national parties actually talk about CP issues in their manifestos. Using a unique data set based on manually coded 812 manifestos written by 95 different parties in 47 regions in Germany, Spain, The Netherlands, and the United Kingdom between 2007 and 2016, it is argued that several party-level characteristics are decisive for sub-national parties' emphasis of CP issues. Even though sub-national parties emphasize CP issues only to a small degree, the results of multilevel mixed-effects Tobit regressions show that it is particularly regional government parties which emphasize CP issues when drafting their regional election manifestos.
Keywords: 330; cohesion policy; salience; manifestos; regional level; sub-national politics; parties